Hands - on yummy chocolate / Rabiatul Adawiyah Abd Rahman - Abd Rahman, Rabiatul Adawiyah (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2019)
Making one's own chocolate is a fun way of learning especially when it takes place outside the campus. Discovering the simplest method in making chocolate candy as a gift for Mother's Day celebration and Eid was shared by the owner of Chocenwrapper Chocolate House in Jitra, Kedah. The one-day trip was packed with exciting activities. Students get to know the industrial size chocolate production equipment such as tempering machine, moulding machines and cooling machines as well as the processes involved in making chocolates. They also had fun by engaging in a special session of hands-on activities of making their own chocolate. "This trip was an eye opener for the students of Pastry Arts program as they gain the knickknack for their future business or career in the world of chocolates The academic visit ended with more chocolate product shopping spree within the factory outlet shop. This trip was an eye opener for the students of Pastry Arts program as they do not only gain the knowledge in chocolate processing by visiting the factory but also the knickknack for their future business or career in the world of chocolates.